Heat and flow analysis of a water droplet on hydrophobic and hydrophilic phase change material. (July 2018) - Al-Sharafi, Abdullah; Yilbas, Bekir S.; Ali, H.
Highlights: Surface wetting characteristics reverses upon melting/solidification of n-octadecane. Droplet flow field changes during the melting of n-octadecane at droplet bottom. Nusselt number shows two distinct regions at droplet bottom. Nusselt number remains lower in early heating period. Abstract: Droplet heat transfer is examined incorporating the phase change material on the hydrophobic surface. Solvent crystallization of polycarbonate wafer is carried out and functionalized silica particles are deposited on the crystallized surface to achieve high water droplet contact angle (125°) with low hysteresis (2°). N-octadecane is used as a phase change material, which is introduced to form a thin layer on the functionalized silica coated surface. Flow and heat transfer analysis are carried out inside the droplet during the melting/solidification of the phase change material. It is found that thin layer deposition of n-octadecane on the treated surface gives rise to reversible hydrophobic-hydrophilic switching surface characteristics. In this case, the state of the treated surface becomes hydrophilic when the phase change material melts on the surface and it recoverably reverses to hydrophobic state when the surface solidifies. Inside the droplet, a single circulation cell is formed during the phase change of n-octadecane coating along the contact line at the droplet bottom. The center of circulation cell moves towards the solid phase side of the phase change material as the phase change progresses along the contact line. The Nusselt number increases with increasing size of the liquid phase on the droplet bottom. The Nusselt number demonstrates two distinguishing regions at the droplet bottom. In the first region, heat is transferred from the liquid phase of the phase change material to the droplet liquid while in the second region heat transfer reverses towards the solid phase of the phase change material, which is associated with the attainment of higher droplet fluid temperature than that of the solid phase change material surface.